Formulasi gel ekstrak daun sirih cina (Peperomia pellucida L. Kunth) variasi carbopol 940 serta uji fisik dan stabilitasnya - Anggoro, Novita; Endriyatno, Nur Cholis (Universitas Mataram, 2024)
Chinese betel leaf (Peperomia pellucida L. Kunth) contains tannins, alkaloids, saponins and flavonoids which can inhibit the growth of Propionibacterium acnes bacteria. Gel preparations are suitable for topical therapy of acne. The gelling agent used was carbopol 940. The purpose of this study was to determine the effect and concentration of carbopol 940 which produced the best physical properties of Chinese betel leaf extract gel preparations. This research is an experimental research. Gel preparations were made with various concentrations of carbopol 940 0.5%, 1.0%, 1.5%, and 2.0% then organoleptic examination, homogeneity, pH, adhesion, spreadability, viscosity, skin irritation, physical stability , and hedonic. The data obtained were analyzed with SPSS (trial) using the One Way ANOVA method. The results showed that variations in carbopol 940 concentrations had an effect on organoleptic, adhesiveness, pH, spreadability, viscosity, and hedonics but had no effect on homogeneity, physical stability, and skin irritation. Carbopol 940 concentration of 1.0% produced the best preparation compared to concentrations of 0.5%, 1.5% and 2.0% in terms of physical properties and statistical analysis.